Current collector prime coat binder and preparation method thereof

By crosslinking the polyimide and epoxy resin in the polymerized monomer, a current collector primer adhesive with good NMP and electrolyte resistance was prepared, which solved the inability to solvents and electrolytes of traditional binders. The problem has improved the battery's performance and life.

CN119432308APending Publication Date: 2025-02-14CHANGZHOU HUANFENG ELECTRICAL MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411799905.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional aluminum foil current collector surface adhesives are intolerant to solvents or electrolytes, and there is a risk of corrosion and leakage, affecting the safety and life of the battery.

Method used

Crosslinking of crosslinked polymeric monomers, including polyimide and epoxy resin, is achieved through a low-temperature drying process to prepare a current collector primer adhesive with good NMP resistance and electrolyte resistance.

Benefits of technology

It improves the surface flatness and corrosion resistance of the battery current collector, extends the capacity and life of the battery, and has good storage stability and industrial production prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177788910000111
    Figure BDA0005177788910000111
  • Figure BDA0005177788910000112
    Figure BDA0005177788910000112
  • Figure BDA0005177788910000121
    Figure BDA0005177788910000121
Patent Text Reader

Abstract

The invention belongs to the technical field of binder materials, and particularly relates to a current collector prime coat binder and a preparation method thereof. The first aspect of the invention provides a current collector prime coat binder and a preparation method thereof. The current collector prime coat binder is prepared from the following raw materials: a cross-linking polymerization monomer and a curing accelerator; the crosslinking polymerization monomer comprises polyimide and epoxy resin; the structure of the polyimide comprises carboxyl. The current collector prime coat binder prepared by the invention has good electrolyte tolerance in N-methyl pyrrolidone commonly used in aluminum foil current collector treatment, the dissolution value in an NMP solution is 3.2-5.1%, the dissolution phenomenon is not shown, and the surface flatness and corrosion resistance of a battery current collector are improved, so that the capacity of a battery is improved, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesive materials, and more specifically relates to a current collector primer adhesive and a preparation method thereof. Background Art

[0002] Primer is a protective layer applied on the metal surface, which can make the metal surface smoother and protect the metal from oxidation, corrosion and pollution. Primer binders are usually made of polymer materials such as polyacrylic resin and polyester resin. In the manufacturing process of battery current collectors, primer binders can improve the surface smoothness and corrosion resistance of battery current collectors, thereby improving the capacity and life of the battery.

[0003] After the aluminum foil current collector has been treated by the primer process, the positive electrode material is coated. The organic solvent currently used for the positive electrode material is NMP (N-methylpyrrolidone). NMP is a highly polar and corrosive solvent. When polyacrylic acid and polyester primer adhesives are used, the primer adhesive is at risk of being corroded and leaking, thus posing a hidden danger to battery safety. Polyimide, as a type of high-performance special engineering plastic, is mostly used in electronics, aerospace, rail transportation and other fields. It has excellent solvent resistance. Common aromatic polyimides are often difficult to dissolve in organic solvents, including NMP. General polyimide solutions actually need to be heated to 300-350°C for thermal imidization, and the precursor polyamic acid solution of the aluminum foil current collector often cannot withstand such high temperatures.

[0004] Therefore, solving the problem of intolerance of the surface adhesive of the traditional aluminum foil current collector to solvents or electrolytes is still a relatively large difficulty currently faced. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present invention proposes a current collector primer adhesive and a preparation method thereof, wherein the preparation raw materials include a cross-linking polymerization monomer and a curing accelerator; the cross-linking polymerization monomer includes polyimide and epoxy resin; and the polyimide contains a carboxyl group in its structure.

[0006] The coating process is achieved through polyimide and epoxy resin, and the cross-linking of polyimide and epoxy resin is achieved through a low-temperature drying process, ultimately achieving good NMP tolerance and electrolyte tolerance of the primer adhesive.

[0007] In some embodiments, the preparation method of polyimide includes adding the first reaction unit and the second reaction unit into NMP at a certain molar ratio, then adding a catalyst, performing a polymerization reaction at a certain temperature to obtain a carboxyl-terminated polyimide with a certain solid content, and titrating the acid value.

[0008] In some embodiments, the raw materials for preparing the polyimide include, by molar parts, 0.5-2 mol of a first reaction unit, 0.5-2 mol of a second reaction unit, 0.001-0.5 mol of a catalyst, and 5-15 mol of a solvent.

[0009] In some embodiments, the first reaction unit includes one or more of trimellitic anhydride (TMA), pyromellitic dianhydride (PMDA), ketone anhydride (BTDA), diphenyl ether dianhydride (ODPA), biphenyl dianhydride (BPDA), and naphthalenetetracarboxylic dianhydride (NTDA).

[0010] In some embodiments, the first reaction unit includes one or two of metaphthalic anhydride (TMA), pyromellitic anhydride (PMDA), ketone anhydride (BTDA), diphenyl ether anhydride (ODPA), biphenyl anhydride (BPDA), and naphthalenetetracarboxylic anhydride (NTDA).

[0011] In some embodiments, the first reaction unit includes two of metaphthalic anhydride (TMA), pyromellitic anhydride (PMDA), ketone anhydride (BTDA), diphenyl ether anhydride (ODPA), biphenyl anhydride (BPDA), and naphthalenetetracarboxylic anhydride (NTDA).

[0012] In some embodiments, the second reaction unit includes one or more of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), and lysine diisocyanate (LDI).

[0013] In some embodiments, the catalyst includes one or more of triethylamine, triethylenediamine, ethyl tin octoate, dibutyltin dilaurate, lead octoate, iron octoate, cobalt octoate, tetraisobutyl titanate, potassium fluoride, and potassium chloride.

[0014] In some embodiments, the mass of the catalyst accounts for 0.5-1.0% of the mass of the first reaction unit.

[0015] In some embodiments, the molar ratio of the first reaction unit to the second reaction unit is 1:(0.9-1).

[0016] More preferably, the molar ratio of the first reaction unit to the second reaction unit is 1:(0.94-0.96).

[0017] The ones that can be listed include 1:0.94, 1:0.95, and 1:0.96.

[0018] In some embodiments, the polymerization reaction temperature is 90-120°C.

[0019] Examples include 90°C, 95°C, 98°C, 100°C, 105°C, 110°C, 115°C, 118°C, and 120°C.

[0020] In some embodiments, the viscosity of the carboxyl-terminated polyimide is 2000-3000 cP (Brookfeld-DV2T, #21 rotor, 25° C.).

[0021] Examples include 2000cP, 2200cP, 2300cP, 2500cP, 2650cP, 2700cP, 2800cP, 2850cP, 2900cP, 2920cP, 2970cP, and 3000cP.

[0022] In some embodiments, the solid content of the carboxyl-terminated polyimide is 25 to 30 wt %.

[0023] Examples include 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, and 30wt%.

[0024] In some embodiments, the acid value of the carboxyl-terminated polyimide is 8.5 to 9.5 mgKOH / g.

[0025] Examples include 8.5 mgKOH / g, 8.6 mgKOH / g, 8.7 mgKOH / g, 8.8 mgKOH / g, 8.9 mgKOH / g, 9.0 mgKOH / g, 9.1 mgKOH / g, 9.2 mgKOH / g, 9.3 mgKOH / g, 9.4 mgKOH / g, and 9.5 mgKOH / g.

[0026] In some embodiments, the epoxy resin includes bisphenol A epoxy resin or novolac epoxy resin.

[0027] In some embodiments, the curing accelerator includes one or more of a quaternary ammonium salt, triphenylphosphine, and triethylamine.

[0028] In some embodiments, the molar ratio of the carboxyl group in the carboxyl-terminated polyimide to the epoxy group in the epoxy resin is 1:(1.2-1.4).

[0029] The ones that can be listed include 1:1.2, 1:1.3, and 1:1.4.

[0030] In some embodiments, the mass of the curing accelerator accounts for 1-2% of the mass of the epoxy resin.

[0031] In some embodiments, the raw materials for preparation include, by weight: 800-1200 parts of carboxyl-terminated polyimide, 20-80 parts of epoxy resin, 0.2-1.6 parts of curing accelerator, and 50-200 parts of solvent.

[0032] In some embodiments, the solvent comprises NMP.

[0033] A second aspect of the present invention provides a method for preparing a current collector primer adhesive, comprising the following steps:

[0034] S1: mixing a carboxyl-terminated polyimide resin solution and an epoxy resin in a certain proportion to obtain a mixed solution;

[0035] S2: dissolve the curing accelerator in a solvent, add the mixed solution obtained in S1, stir, and filter to obtain the product.

[0036] In some embodiments, the mixing and stirring conditions in S1 include: a temperature of 20 to 30° C. and a time of 4 to 5 hours.

[0037] Temperatures that may be cited include 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, and 30°C.

[0038] The times that can be cited include 4 hours, 4.2 hours, 4.5 hours, 4.7 hours, 4.8 hours, and 5 hours.

[0039] In some embodiments, the stirring time in S2 is 2 to 3 hours.

[0040] In some embodiments, the filtration is performed using a filter with a pore size of 100 to 200 meshes.

[0041] Beneficial effects:

[0042] 1. The current collector primer binder prepared by the present invention has good electrolyte tolerance in N-methylpyrrolidone commonly used in aluminum foil current collector processing, and the dissolution value in NMP solution is 3.2-5.1%, and does not show dissolution phenomenon, thereby improving the surface flatness and corrosion resistance of the battery current collector, thereby improving the capacity and life of the battery.

[0043] 2. The current collector binder prepared by the present invention has good storage stability. Its viscosity does not change significantly when stored at 60°C for 4 weeks, and does not affect the preparation of the battery current collector. It has good application value and industrial production prospects.

[0044] 3. The current collector binder prepared by the present invention has a simple process, and the polyimide is terminated with carboxyl groups by chemical cross-linking to ensure further cross-linking with epoxy resin, and the prepared binder has stable chemical properties.

[0045] 4. The current collector adhesive prepared by the present invention needs to control the feed ratio and compounding temperature of the carboxyl-terminated polyimide and the epoxy resin as well as the feed amount of the curing accelerator, otherwise the prepared adhesive will have the risk of gelling and cannot be used to prepare batteries. DETAILED DESCRIPTION

[0046] Example

[0047] Example 1

[0048] A current collector primer adhesive is prepared by using raw materials including 1000 g of carboxyl-terminated polyimide, 43.11 g of epoxy resin, 0.45 g of a curing accelerator, and 129 g of a solvent.

[0049] Carboxyl terminated polyimide

[0050] The carboxyl-terminated polyimide is homemade, and the raw materials and dosages are as follows:

[0051] The raw materials for preparing the carboxyl-terminated polyimide include, by mole, 1.1 mol of a first reaction unit, 1.04 mol of a second reaction unit, 0.1 mol of a catalyst, and 11.7 mol of a solvent.

[0052] The first reaction unit comprises TMA and BPDA, and the molar ratio of TMA to BPDA is 1:0.1;

[0053] The second reaction unit is MDI;

[0054] The catalyst is triethylamine;

[0055] The solvent is NMP;

[0056] The preparation method of the carboxyl-terminated polyimide comprises the following steps:

[0057] In a reaction kettle, TMA, BPDA, triethylamine and NMP solvent were added respectively, stirred at 90°C for half an hour, MDI was added, stirred for 1 hour, the temperature was raised to 120°C, and stirring was continued for 4 hours to obtain carboxyl-terminated polyimide with a viscosity of 2600 cP (Brookfeld-DV2T, #21 rotor, 25°C), a solid content of 25% wt, and an acid value of 8.7 mgKOH / g.

[0058] Epoxy resin

[0059] Model: Phoenix 6101, purchased from Jiangyin Wanqian Chemicals Co., Ltd., epoxy equivalent 210-230 g / mol.

[0060] Curing accelerator

[0061] Triphenylphosphine

[0062] Solvents

[0063] NMP

[0064] A method for preparing a current collector primer binder comprises the following steps:

[0065] In a stirring kettle equipped with circulating liquid cooling, the circulating temperature was controlled at 25±1°C, carboxyl-terminated polyimide and epoxy resin were added, and stirred for 4 hours.

[0066] The curing accelerator was added to NMP, stirred and dissolved, and then added to the stirring kettle, and the stirring was continued for 1 hour. After the stirring was completed, the slurry was collected through a filter bag with a pore size of 150 meshes to obtain a primer adhesive with a solid content of 25wt%.

[0067] Example 2

[0068] A current collector primer adhesive is prepared by using raw materials including 1000 g of carboxyl-terminated polyimide, 37.05 g of epoxy resin, 0.4 g of a curing accelerator, and 95 g of a solvent.

[0069] Carboxyl terminated polyimide

[0070] The carboxyl-terminated polyimide is homemade, and the raw materials and dosages are as follows:

[0071] The raw materials for preparing the carboxyl-terminated polyimide include, by mole, 1.1 mol of a first reaction unit, 1.04 mol of a second reaction unit, 0.003 mol of a catalyst, and 7.8 mol of a solvent.

[0072] The first reaction unit includes TMA and PMDA, and the molar ratio of TMA to PMDA is 1:0.1;

[0073] The second reaction unit is TDI;

[0074] The catalyst is tetraisobutyl titanate;

[0075] The solvent is NMP;

[0076] The preparation method of the carboxyl-terminated polyimide comprises the following steps:

[0077] In a reaction kettle, TMA, PMDA, tetraisobutyl titanate and NMP solvent were added respectively, stirred at 90°C for half an hour, TDI was added, stirred for 1 hour, the temperature was raised to 120°C, and stirring was continued for 4 hours to obtain carboxyl-terminated polyimide with a viscosity of 2700 cP (Brookfeld-DV2T, #21 rotor, 25°C), a solid content of 28% wt, and an acid value of 9.1 mgKOH / g.

[0078] Epoxy resin

[0079] Model: NPEL-128, purchased from Jiangyin Wanqian Chemicals Co., Ltd., epoxy equivalent weight 184-190 g / mol.

[0080] Curing accelerator

[0081] Tetrabutylammonium bromide

[0082] Solvents

[0083] NMP

[0084] A method for preparing a current collector primer binder comprises the following steps:

[0085] In a stirring kettle equipped with circulating liquid cooling, the circulating temperature was controlled at 25±1°C, carboxyl-terminated polyimide and epoxy resin were added, and stirred for 4 hours.

[0086] The curing accelerator was added to NMP, stirred and dissolved, and then added to the stirring kettle, and the stirring was continued for 1 hour. After the stirring was completed, the slurry was collected through a filter bag with a pore size of 150 meshes to obtain a primer adhesive with a solid content of 28 wt%.

[0087] Example 3

[0088] A current collector primer adhesive is prepared by using raw materials including 1000 g of carboxyl-terminated polyimide, 39.28 g of epoxy resin, 0.4 g of a curing accelerator, and 91.65 g of a solvent.

[0089] Carboxyl terminated polyimide

[0090] The carboxyl-terminated polyimide is homemade, and the raw materials and dosages are as follows:

[0091] The raw materials for preparing the carboxyl-terminated polyimide include, by mole, 1.1 mol of a first reaction unit, 1.04 mol of a second reaction unit, 0.015 mol of a catalyst, and 10.5 mol of a solvent.

[0092] The first reaction unit comprises TMA and BTDA, and the molar ratio of TMA to BTDA is 1:0.1;

[0093] The second reaction unit is IPDI;

[0094] The catalyst is potassium chloride;

[0095] The solvent is NMP;

[0096] The preparation method of the carboxyl-terminated polyimide comprises the following steps:

[0097] In a reaction kettle, TMA, BTDA, potassium chloride and NMP solvent were added respectively, stirred at 90°C for half an hour, IPDI was added, stirred for 1 hour, the temperature was raised to 120°C, and stirring was continued for 4 hours to obtain carboxyl-terminated polyimide with a viscosity of 2900 cP (Brookfeld-DV2T, #21 rotor, 25°C), a solid content of 30 wt%, and an acid value of 9.4 mgKOH / g.

[0098] Epoxy resin

[0099] Model: E51, purchased from Shandong Pinshang New Materials Co., Ltd., epoxy equivalent 184-195 g / mol.

[0100] Curing accelerator

[0101] Triethylamine

[0102] Solvents

[0103] NMP

[0104] A method for preparing a current collector primer binder comprises the following steps:

[0105] In a stirring kettle equipped with circulating liquid cooling, the circulating temperature was controlled at 25±1°C, carboxyl-terminated polyimide and epoxy resin were added, and stirred for 4 hours.

[0106] The curing accelerator was added to NMP, stirred and dissolved, and then added to the stirring kettle, and the stirring was continued for 1 hour. After the stirring was completed, the slurry was collected through a filter bag with a pore size of 150 meshes to obtain a primer adhesive with a solid content of 30wt%.

[0107] Comparative Example 1

[0108] A binder, the specific implementation manner of which is the same as that of Example 1, except that only carboxyl-terminated polyimide is prepared.

[0109] Comparative Example 2

[0110] A binder is prepared from raw materials including 1000 g of carboxyl-terminated polyimide, 43.11 g of epoxy resin, 1.35 g of a curing accelerator, and 129 g of a solvent.

[0111] Carboxyl terminated polyimide

[0112] The carboxyl-terminated polyimide is homemade, and the raw materials and dosages are as follows:

[0113] The raw materials for preparing the carboxyl-terminated polyimide include, by mole, 1.1 mol of a first reaction unit, 1.04 mol of a second reaction unit, 0.1 mol of a catalyst, and 11.7 mol of a solvent.

[0114] The first reaction unit comprises TMA and BPDA, and the molar ratio of TMA to BPDA is 1:0.1;

[0115] The second reaction unit is MDI;

[0116] The catalyst is triethylamine;

[0117] The solvent is NMP;

[0118] The preparation method of the carboxyl-terminated polyimide comprises the following steps:

[0119] In a reaction kettle, TMA, BPDA, triethylamine and NMP solvent were added respectively, stirred at 90°C for half an hour, MDI was added, stirred for 1 hour, the temperature was raised to 120°C, and stirring was continued for 4 hours to obtain carboxyl-terminated polyimide with a viscosity of 2600 cP (Brookfeld-DV2T, #21 rotor, 25°C), a solid content of 25% wt, and an acid value of 8.7 mgKOH / g.

[0120] Epoxy resin

[0121] Model: Phoenix 6101, purchased from Jiangyin Wanqian Chemicals Co., Ltd., epoxy equivalent 210-230 g / mol.

[0122] Curing accelerator

[0123] Triphenylphosphine

[0124] Solvents

[0125] NMP

[0126] A method for preparing a binder comprises the following steps:

[0127] In a stirring kettle equipped with circulating liquid cooling, the circulating temperature was controlled at 80±1°C, carboxyl-terminated polyimide and epoxy resin were added, and stirred for 4 hours.

[0128] The curing accelerator was added to NMP, stirred and dissolved, and then added to the stirring kettle, and the stirring was continued for 12 hours. After the stirring was completed, the slurry was collected through a filter bag with a pore size of 150 meshes to obtain a binder with a solid content of 25wt%.

[0129] Comparative Example 3

[0130] A current collector primer adhesive is prepared by using raw materials including 1000 g of carboxyl-terminated polyimide, 43.11 g of epoxy resin, 1.35 g of a curing accelerator, and 129 g of a solvent.

[0131] Carboxyl terminated polyimide

[0132] The carboxyl-terminated polyimide is homemade, and the raw materials and dosages are as follows:

[0133] The raw materials for preparing the carboxyl-terminated polyimide include, by mole, 1.1 mol of a first reaction unit, 1.04 mol of a second reaction unit, 0.1 mol of a catalyst, and 11.7 mol of a solvent.

[0134] The first reaction unit comprises TMA and BPDA, and the molar ratio of TMA to BPDA is 1:0.1;

[0135] The second reaction unit is MDI;

[0136] The catalyst is triethylamine;

[0137] The solvent is NMP;

[0138] The preparation method of the carboxyl-terminated polyimide comprises the following steps:

[0139] In a reaction kettle, TMA, BPDA, triethylamine and NMP solvent were added respectively, stirred at 90°C for half an hour, MDI was added, stirred for 1 hour, the temperature was raised to 120°C, and stirring was continued for 4 hours to obtain carboxyl-terminated polyimide with a viscosity of 2600 cP (Brookfeld-DV2T, #21 rotor, 25°C), a solid content of 25% wt, and an acid value of 8.7 mgKOH / g.

[0140] Epoxy resin

[0141] Model: Phoenix 6101, purchased from Jiangyin Wanqian Chemicals Co., Ltd., epoxy equivalent 210-230 g / mol.

[0142] Curing accelerator

[0143] Triphenylphosphine

[0144] Solvents

[0145] NMP

[0146] A method for preparing a current collector primer binder comprises the following steps:

[0147] In a stirring kettle equipped with circulating liquid cooling, the circulating temperature was controlled at 25±1°C, carboxyl-terminated polyimide and epoxy resin were added, and stirred for 4 hours.

[0148] The curing accelerator was added to NMP, stirred and dissolved, and then added to the stirring kettle, and the stirring was continued for 1 hour. After the stirring was completed, the slurry was collected through a filter bag with a pore size of 150 meshes to obtain a primer adhesive with a solid content of 25wt%.

[0149] Comparative Example 4

[0150] A binder is prepared from raw materials including 1000 g of carboxyl-terminated polyimide, 57.17 g of epoxy resin, 0.57 g of a curing accelerator, and 171.51 g of a solvent.

[0151] Carboxyl terminated polyimide

[0152] The carboxyl-terminated polyimide is homemade, and the raw materials and dosages are as follows:

[0153] The raw materials for preparing the carboxyl-terminated polyimide include, by mole, 1.1 mol of a first reaction unit, 1.04 mol of a second reaction unit, 0.1 mol of a catalyst, and 11.7 mol of a solvent.

[0154] The first reaction unit comprises TMA and BPDA, and the molar ratio of TMA to BPDA is 1:0.1;

[0155] The second reaction unit is MDI;

[0156] The catalyst is triethylamine;

[0157] The solvent is NMP;

[0158] The preparation method of the carboxyl-terminated polyimide comprises the following steps:

[0159] In a reaction kettle, TMA, BPDA, triethylamine and NMP solvent were added respectively, stirred at 90°C for half an hour, MDI was added, stirred for 1 hour, the temperature was raised to 120°C, and stirring was continued for 4 hours to obtain carboxyl-terminated polyimide with a viscosity of 2600 cP (Brookfeld-DV2T, #21 rotor, 25°C), a solid content of 25% wt, and an acid value of 8.7 mgKOH / g.

[0160] Epoxy resin

[0161] Model: Phoenix 6101, purchased from Jiangyin Wanqian Chemicals Co., Ltd., epoxy equivalent 210-230 g / mol.

[0162] Curing accelerator

[0163] Triphenylphosphine

[0164] Solvents

[0165] NMP

[0166] A method for preparing a binder comprises the following steps:

[0167] In a stirring kettle equipped with circulating liquid cooling, the circulating temperature was controlled at 25±1°C, carboxyl-terminated polyimide and epoxy resin were added, and stirred for 4 hours.

[0168] The curing accelerator was added to NMP, stirred and dissolved, and then added to the stirring kettle, and the stirring was continued for 1 hour. After the stirring was completed, the slurry was collected through a filter bag with a pore size of 150 meshes to obtain a binder with a solid content of 25wt%.

[0169] Comparative Example 5

[0170] A binder is prepared by adding acrylic acid monomer (50 g), propionamide monomer (50 g), ammonium persulfate (0.5 g), and 567 g of deionized water, respectively, and stirring at 60° C. for 6 hours to obtain an acrylic acid-acrylamide copolymer solution with a solid content of 15 wt %.

[0171] Performance Testing

[0172] The prepared adhesive was coated on a glass plate and then dried in a 120° C. forced air oven for 2 hours, with the coating slit controlled to obtain a dry film with a thickness of 7 to 10 μm. The obtained adhesive film was then tested.

[0173] 1. NMP tolerance test

[0174] The primer film with a gram weight of 1.5 g prepared in Examples 1-3 and Comparative Examples 1-5 was placed in NMP and placed in a 60°C oven. It was allowed to stand for one hour. The film was then taken out and soaked in ethanol to replace the solvent. It was then dried at 60°C for half an hour. The weight was weighed and the dissolution value was calculated.

[0175] Dissolution value = (film mass - dry weight of film after NMP immersion) / film mass × 100%

[0176] 2. Electrolyte tolerance test

[0177] The primer film with a weight of 1.5 g prepared in Examples 1-3 and Comparative Examples 1-5 was placed in an electrolyte and placed in a 60°C oven for 24 hours. The film was then taken out, soaked in DMC solvent to replace the solvent, and then dried at 80°C for half an hour. The weight was weighed and the dissolution value was calculated.

[0178] Dissolution value = (film mass - dry weight of film after immersion in electrolyte) / film mass × 100%

[0179] The electrolyte mentioned above is EC (ethylene carbonate): EMC (ethyl methyl carbonate): DEC (diethyl carbonate) in a weight ratio of 5:3:2;

[0180] Performance test results are shown in Table 1

[0181] Table 1:

[0182]

[0183] According to the above test method, it is not difficult to find that the prepared examples and comparative examples have good electrolyte tolerance, but have great differences in NMP tolerance. Specifically, the end-capped polyimide in comparative example 1 has poor tolerance in NMP and will redissolve because it is an NMP-soluble polymer.

[0184] Examples 1 to 3 and Comparative Examples 2 to 4 are polymers obtained by crosslinking the end-capped polyimide with the cyclic resin, and all exhibit good NMP tolerance, with dissolution values ​​ranging from 3.2 to 5.1%.

[0185] Comparative Example 5 is an acrylic copolymer, which is completely dissolved even after being immersed in NMP for a long time.

[0186] 3. Stability test

[0187] 1) Viscosity test: The adhesives prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to viscosity test, test method: Brookfeld-DV2T, #21 rotor, 25° C., and the test results are recorded in Table 2 below;

[0188] 2) Stability test: The adhesives prepared in Examples 1-3 and Comparative Examples 1-5 were placed in a vacuum oven at 60°C and left to stand for 1 week, 2 weeks, 3 weeks and 4 weeks respectively, and the changes in viscosity were observed. The corresponding viscosities were recorded in Table 2 below.

[0189] Wherein, the polyimide prepared in Comparative Example 1 was not recorded for the final viscosity;

[0190] Comparative Example 5 is a conventional acrylic adhesive and no final viscosity record was performed.

[0191]

[0192]

[0193] The storage stability of the adhesive was tested. Under storage conditions of 60° C., the viscosity of Examples 1 to 3 increased only slightly within 4 weeks, which did not affect the process implementation.

[0194] In Comparative Example 2, the high temperature (80° C.) was maintained during the blending stage of the carboxyl-terminated polyimide and the epoxy resin, and the amount of the curing accelerator was increased to 3% of the mass of the epoxy resin. The viscosity of the adhesive discharge was too high, and there was a risk of gelation after subsequent storage.

[0195] In comparative example 3, the amount of curing accelerator is increased to 3% of the mass of the epoxy resin. As the storage time increases, there is a risk of viscosity increase or even gelation.

[0196] Comparative Example 4, the weight ratio of epoxy resin and carboxyl-terminated polyimide increased, and there was also a risk of viscosity increase and even gelation as the storage time increased.

[0197] In summary, the current collector primer binder proposed in the present invention needs to control the feed ratio and compounding temperature of carboxyl-terminated polyimide and epoxy resin and the feed amount of curing accelerator. The primer binder proposed in the present invention has good NMP tolerance and electrolyte tolerance.

Claims

1. A current collector primer binder, characterized in that: The preparation raw materials include cross-linking polymerization monomers and curing accelerators; the cross-linking polymerization monomers include polyimide and epoxy resin; and the structure of the polyimide contains carboxyl groups.

2. The current collector primer binder according to claim 1, characterized in that: The polyimide is a carboxyl-terminated polyimide.

3. The current collector primer binder according to claim 1 or 2, characterized in that: The molar ratio of the carboxyl group in the polyimide to the epoxy group in the epoxy resin is 1:(1.2-1.4).

4. The current collector primer binder according to claim 1 or 2, characterized in that: The acid value of the polyimide is 8.5 to 9.5 mgKOH / g.

5. The current collector primer binder according to claim 4, characterized in that: The viscosity of the polyimide at 25° C. is 2000 to 3000 cP.

6. The current collector primer binder according to claim 1, characterized in that: The mass of the curing accelerator accounts for 1-2% of the mass of the epoxy resin.

7. The current collector primer binder according to claim 6, characterized in that: The epoxy resin includes one or both of bisphenol A epoxy resin and novolac epoxy resin.

8. The current collector primer binder according to claim 1, characterized in that: The viscosity of the primer adhesive at 25° C. is 1500-2500 cP.

9. A method for preparing a current collector primer binder according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: Mixing and stirring polyimide and epoxy resin to obtain a mixed solution; S2: dissolve the curing accelerator in a solvent, add the mixed solution obtained in S1, stir, and filter to obtain the product.

10. The method for preparing a current collector primer binder according to claim 9, characterized in that: The mixing and stirring conditions in S1 include: a temperature of 20 to 30° C. and a time of 4 to 5 hours; and the stirring time in S2 is 2 to 3 hours.